Digital Tools in Teaching High School Students - Truten, Alina (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article examines the use of digital tools in teaching high school students. The purpose of scientific research is to analyze the current state of the use of digital tools in the education of high school students and determine the prospects for their implementation to improve the efficiency of the educational process. The objectives of the study are: to analyze modern approaches to the use of digital tools in the education of high school students; to classify digital tools by type according to their functional load in the educational process; to characterize the functional capabilities of digital platforms and services used in the education of high school students. To achieve the goal and the identified tasks, the following methods were used: analysis and generalization; comparative analysis; method of expert assessments; observation; and system analysis. Modern approaches to the use of digital tools in education that contribute to personalization, flexibility, and increased efficiency of the educational environment are analyzed. Digital tools are classified by type according to their functional purpose and role in forming students’ key competencies: tools for creating visual and multimedia content; interactive learning and gamification; collaboration and project management; communication and sharing of materials; organization and storage of educational content. The functional capabilities of the main digital platforms and services most often used in high school, particularly for organizing distance and blended learning, are described: Canva, Google services, Telegram, Pinterest, Genially, InShot, Trello, Wakelet, Mentimeter, Flip, Figma, and Kahoot. The importance of using digital technologies to ensure a high-quality and competitive educational environment is emphasized. It is concluded that the comprehensive implementation of these tools allows you to adapt the educational process to the needs of the modern generation, make it more flexible, personalized and effective.